2002
DOI: 10.1191/0269215502cr545oa
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effectiveness of intensive multidisciplinary rehabilitation for people with Parkinson's disease and their carers

Abstract: This intensive co-ordinated programme provided immediate benefits to people with Parkinson's disease and their carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 20 publications
5
112
2
9
Order By: Relevance
“…11 There are several studies of multidisciplinary care in Parkinson's disease comparing outcomes before and after the intervention. Outpatient multidisciplinary care programmes have reported shortterm improvements in UPDRS motor score, 12 gait speed and stride length, [13][14] speech, depression and health-related quality of life. 13 low up) have also been reported, and the authors comment that close multidisciplinar y working was key to success.…”
Section: Effectiveness Of Multidisciplinary Carementioning
confidence: 99%
See 1 more Smart Citation
“…11 There are several studies of multidisciplinary care in Parkinson's disease comparing outcomes before and after the intervention. Outpatient multidisciplinary care programmes have reported shortterm improvements in UPDRS motor score, 12 gait speed and stride length, [13][14] speech, depression and health-related quality of life. 13 low up) have also been reported, and the authors comment that close multidisciplinar y working was key to success.…”
Section: Effectiveness Of Multidisciplinary Carementioning
confidence: 99%
“…Outpatient multidisciplinary care programmes have reported shortterm improvements in UPDRS motor score, 12 gait speed and stride length, [13][14] speech, depression and health-related quality of life. 13 low up) have also been reported, and the authors comment that close multidisciplinar y working was key to success. 15 Inpatient multidisciplinar y rehabilitation for Parkinson's disease has also been reported to be effective in studies using a trial design comparing pre-and postintervention outcomes.…”
Section: Effectiveness Of Multidisciplinary Carementioning
confidence: 99%
“…Eleven studies conducted various interventions, including drugs [69,65,70,73], provision of communitybased nurse specialists [66], provision of instructions of clinical guidelines to neurologists [67], standardised pharmaceutical care [72], adherent therapy [64], deep brain stimulation (DBS) surgery [76], and multidisciplinary rehabilitation [74]. developed by Rosser and colleagues in 1970s, is comprised of eight levels of disability (loss of function and mobility) and four levels of subjective distress, describing 29 disability/distress states [77,78].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies showed consistency between the EQ-5D-3L and the reference measures in terms of the evidence for whether there was a statistically significant change overtime; the reference measures included UPDRS part II ADL [65], PDQ-39 [66,67,76], PDQ-8 and H&Y [68], and HAD depression [74].…”
Section: Assessment Of Responsivenessmentioning
confidence: 99%
“…Recently, investigators have advocated for a more multidisciplinary approach to the care of individuals with PD [31][32][33][34][35]. Two studies from the Royal Surrey County Hospital in the United Kingdom have demonstrated that short-term multidisciplinary services positively affect quality of life and behavioral outcomes [34][35].…”
Section: Discussionmentioning
confidence: 99%